Dynamic Analysis of Impulsive Differential Chaotic System and Its Application in Image Encryption - Junrong Guo; Xiaolin Liu; Ping Yan (Mathematics, 2023)
In this paper, we study the dynamic behavior of an impulse differential chaotic system which can be applied to image encryption. Combined with the chaotic characteristics of the high dimensional impulsive differential equations, the plaintext image can be encrypted by using the traditional Henon map and diffusion sequences encryption algorithm. The initial values and control parameters serve as keys for encryption algorithms, and the algorithm has a larger key space. The key is resistant to minor interference and the accuracy can reach <semantics>10−12</semantics>. The simulation results show that the impulsive differential chaotic system has a good application prospect in image encryption.